Evaluation of the therapeutic effect of pomegranate peel ginger ultrafine powder on chronic enteritis in mice by regulating intestinal microbiota - Zhenhuan Guo; Xiaohua Wang; Xiaohua Wang; Yupeng Li; Yanling Zhang; Yanling Zhang; Peng Guo; Jicheng Zhang; Zhiqiang Zhang; Xia Ma; Xia Ma (Frontiers in Immunology)
To explore the efficacy and mechanism of Pomegranate peel Ginger ultrafine powder (PG) in treating chronic enteritis in mice. Sixty SPF-grade mice were randomly divided into a blank group, a model group, loperamide hydrochloride group (5 mg/kg), a high-dose PG group (100 mg/kg), a medium-dose group (50 mg/kg), and a low-dose group (25 mg/kg), with 10 mice in each group and an equal number of males and females. A chronic enteritis mouse model was established using a multifactorial method of low temperature + ice water + castor oil. The blank group was given an equal amount of physiological saline intragastrically, while the other groups were intervened with corresponding drugs for 7 consecutive days. After 7 days, samples were collected, and Enzyme-linked immunosorbent assay (ELISA) was used to detect the levels of interleuckin 1β (IL-1β), IL-6, and Tumor necrosis factorα(TNF-α) in mouse serum. HE staining was used to examine the pathological changes in the small intestine. oxidative reagent kits were used to detect the content of total superoxide dismutase(T-SOD) and Malondialdehyde (MDA) in the small intestine. Western blot was used to detect the expression of Aquaporin 8(AQP8) proteins in the small intestine. Real time quantitative reverse transcription polymerase chain reaction (RT-qPCR) was used to detect the expression of AQP3, AQP4, AQP8, and Sodium/hydrogen exchanger 8 (NHE8) genes in the small intestine. metagenomics was used to detect the gut microbiota in mouse feces. Compared with the model group, all doses of PG groups reduced the levels of IL-1β, IL-6, and TNF-α in mouse serum (P<0.05), improved pathological changes in the small intestine, increased the content of T-SOD in the small intestine tissue, reduced the content of MDA, increased the expression of AQP4 and AQP8 mRNA, and decreased the expression of AQP3 and NHE8 mRNA (P<0.05), increased the expression of AQP8 protein. PG could improve the pathological changes of chronic enteritis in mice, enhance antioxidant capacity, and alleviate diarrhea caused by chronic enteritis by downregulating the expression of intestinal epithelial transport proteins and acute-phase proteins, and altering gut microbiota.